Bacillus Subtilis HU58 Immobilized in Micropores of Diatomite for Using in Self-healing Concrete. (2017) - Huynh, Nguyen Ngoc Tri; Phuong, Nghi Mai; Toan, Nguyen Phung Anh; Son, Nguyen Khanh
Abstract: Recent studies reveal that using bacteria to mix into concrete material promote generating specific precipitated product. Such product allows improving physio-mechanical properties of concrete materials at both early and later age. This experimental study deals with the use of Bacillus subtilis HU58 and natural diatomite Lam Dong as controlled release agent to formulate bacterial concrete. We investigated self-healing effect during long period of curing time up to 24 months. Given in the result of material analysis, there is an increasing crystallinity of precipitated calcite by bacteria. At a smaller scale in bacteria modified mortar (prismatic samples 40x40x160 mm), both compressive and flexural strengths increase in comparison with those of normal sample, 57 → 61 MPa (in compression) and 9 → 11 MPa (in flexion). At greater scale in bacterial concrete (cube samples 150x150x150 mm), compressive strengths are higher (about 18%) than obtained results of normal concrete sample at age of 2 months. For the reason of better control of process of precipitation, Bacillus subtilis HU58 and nutrient were first immobilized in diatomite Lam Dong, before introducing in cement matrix. We examined self-healing capacity of crack opening that were artificially prepared (1-1.8 mm by width) after early setting of cement mortar. Results of the water permeability test, developed in laboratory presented the evidence of remediating crack and fissure due to bacteria.